Pengaruh Variasi pH HCL dalam Pengasaman Montmorillonit Terhadap Hasil Bleaching Crude Palm Oil - Tiara Fatika Sari; Riri Jonuarti (Journal of Science, Technology, and Innovation, 2026)
Crude Palm Oil (CPO) requires a bleaching process to reduce pigments and free fatty acids (FFA). Montmorillonite as an adsorbent needs acid activation to improve its adsorption capacity. This study aimed to investigate the effect of HCl activation at pH 2, 4, and 6 on the surface morphology of montmorillonite as characterized by Scanning Electron Microscopy (SEM) and its influence on CPO bleaching efficiency. Acid activation was performed using 0.01 M HCl with a slurry titration method. Particle size analysis was conducted using ImageJ software with the length parameter. Results showed that unactivated montmorillonite had a mean particle length of 1054.54 nm with dense and agglomerated morphology. Activation at pH 4 produced the most homogeneous particle distribution with a mean length of 1635.57 nm and a more open surface structure. Bleaching analysis demonstrated that montmorillonite activated at pH 4 generated the lowest FFA content of 1.4% compared to pH 2 and pH 6. These findings indicate that pH 4 activation provides the optimum balance between structural stability, pore opening, and adsorption effectiveness for CPO bleaching.